Epistemic and Existential, E2-sustainability. On the need to un-learn for re-learning in contemporary spaces - Bagga-Gupta, Sangeeta (Frontiers in Communication, 2023)
This paper contributes to a re-thinking, un-learning and re-learning agenda by interrogating some core ideas and assumptions related to contemporary societal and planetary concerns, including concerns within the research enterprise. Transcending a first step that calls for pausing and re-thinking, this paper troubles universalizing vocabularies that naturalize conceptual framings and ways/waves-of-being in research and educational practices. Furthermore, it illuminates the ways in which scholarship has become complicit in re-cycling and re-creating reductionistic ideas that loop back into educational practices. Its overarching argument aligns with an emergent call within research and higher education for going beyond its universalizing monolithic ethos that has become naturalized in contemporary digital-analogue entangled existence. Framed as alternative theorizing that is variously termed post/decolonial/southern thinking, these emergent perspectives are part of introspection that is critically needed in mainstream academia – in particular in the Learning Sciences. This paper argues that this is needed to contribute to both Epistemic and Existential sustainability, i.e., E2-sustainability. E2-sustainability enables transcending issues of environmental-, economic-, social- and cultural-sustainability. E2-sustainability assumes and includes them. Marked through alternative conceptual framings and pushed by a mobile gaze, this theoretical paper argues that major and minor shifts in thinking are needed for attending to contemporary societal and planetary challenges. E2-sustainability in the scholarly realm has relevance for transcending ethnocentrically framed biases and siloed framings of contemporary education and higher education, including teacher-education. Troubling key taken-for-granted universalizing truths and using the areas of language and educational scholarship as illustrative points of departure, it raises concerns regarding the outsourcing of important educational agendas to technologies, including digitalization on the one hand, and concepts that build on contentious assumptions on the other hand. It is such default outsourcing that is troubled through a curiosity-driven multiversal and global-centric mobile gaze wherein northern and southern knowledge-regimes need to be privileged together. The theorizing presented in this paper builds on a Second Wave of Southern Perspectives, SWaSP framing that has relevance for both north-centric and south-centric scholarship, including writing research. Explicitly multi/inter/cross/trans-disciplinary, this work is relevant to epistemic- and existential-sustainability given its non-allegiance to imaginaries of mono-disciplinarity, nation-states or universalism.